Effect of Wet Condition and Aggregates Type Used in Cement-Based Blocks on Mechanical Behavior of Masonry - Janarththan, Paramasivam; Arunjeyan , Rasathurai; Navaratnarajah, Sathiparan (International Journal of Sustainable Construction Engineering and Technology, 2023)
Water penetration into masonry walls can occur in the masonry structures during the rainy climate. Water penetration not only causes discoloration or efflorescence but also can be damaging to material property. Even though several studies from past literature focus on wet conditions effect on brick masonry, but there is limited study on cement block masonry. The present research aimed to evaluate the effect of wet conditions on the mechanical characteristic of cement block, binder mortar and masonry. Where three types of fine aggregates, namely river sand, lateritic soil and manufactured sand were used for masonry block production. For binding mortar, two mortar classes M2 and M6 according to British Standard European Norm were used. Compression, flexural bending, and splitting tensile tests for blocks and binding mortar were performed in dry and wet conditions. Also, compression, direct shear and bond test were performed on masonry prisms in dry and wet conditions. The results demonstrate that a considerable amount of strength reduction was observed in wet conditions. In wet conditions, cement-soil block masonry showed a higher reduction in compression strength and bond strength, but showed lesser shear strength reduction when compared with the other two masonry types. Overall, cement-river sand block masonry has shown better performance in wet conditions.